Crystal structure, Hirshfeld surface analysis, Thermal study and Conduction mechanism of [(C4H9)4P]3Bi2Cl9 compound. (9th July 2019) - Elgahami, H.; Trigui, W.; Oueslati, A.; Lhoste, J.; Hlel, F.
Abstract : A novel tris (tetrabutylphosphonium) nonachlorodibismuthate (III) compound has been synthesized and characterized by a single‐crystal X‐ray diffraction, calorimetric, IR spectroscopy and electrical measurements. X‐ray diffraction analysis at room temperature reveals that the title compound belongs to the monoclinic system with P21 /c space group. The unit cell dimensions are: a = 19.201(6) Å, b = 16.743 (5) Å, c = 22.396 (8) Å, β = 98.96 (2)° and Z = 4. The crystal structure was solved down to R equal to 0.035 for 5597 independent reflections. The crystal package is provided by electrostatic interactions and hydrogen bonds (C‐H …. Cl). Intermolecular interactions present in the grown single crystal were analyzed by Hirshfeld surface and 2‐dimensional fingerprint plot. The differential scanning calorimetry reveals one order–disorder phase transition at 400 ± 5 K.The electrical conductivity were carried out in the frequency range 200 Hz–1 MHz at various temperatures 343–413 K using impedance spectroscopy technique. The obtained results were analyzed by fitting the experimental data to an equivalent circuit model. The temperature dependence of alternating and direct current conductivities confirms the observed phase transition in the calorimetric study; they were described in terms of Arrhenius relation. AC conductivity measurements reveal that the conduction depends on both frequency and temperature, this agrees well with Correlated Barrier Hopping model in phase I and II. Abstract : The conduction mechanism is assured by CBH model.